High-speed marine craft : one hundred knots at sea - Mantle, Peter J. (Cambridge University Press, 2015)
This book details the efforts to build a large naval vessel capable of traveling at one hundred knots. It is the first book to summarize this extensive work from historical and technical perspectives. It explores the unique principles and challenges in the design of high-speed marine craft. This volume explores different hull form concepts, requiring an understanding of the four forces affecting the lift and the drag of the craft. The four forces covered are hydrostatic (buoyancy), hydro-dynamic, aerostatic, and aerodynamic. This text will appeal to naval researchers, architects, graduate students and historians, as well as others generally interested in naval architecture and propulsion.
Keywords: Warships -- Design and construction -- History -- 21st century.; Warships -- Design and construction -- History -- 20th century.; Warships -- Technological innovations -- United States.; Ground-effect machines -- United States -- Design and construction.; Hydrofoil boats -- United States -- Design and construction.; elektronické knihy; electronic books